Bibliometric analysis of studies on adherence to antiretroviral treatment in Latin America in the period 2010 to 2022 - Florido-Torres, Roger (2025)
Introduction. Different studies have evaluated adherence to antiretroviral treatment (ART) in Latin America and the Caribbean, however, this scientific production has not been quantified or described. The objective of this study was to analyze the scientific production and collaboration indicators on ART adherence in Latin America. Methods. We conducted a bibliometric study using the Scopus, LILACS, Scielo and PubMed databases. Original publications were collected: original studies, brief originals, and theses, during the period 2010 - 2022, and whose study population was Latin American. Scientific production was evaluated according to year of publication, scientific journal, author signature, institutional signature, country signature and research design. The collaboration indicators calculated were co-authorship index, number of institutional affiliations index and the international collaboration rate. Results. The search strategy recovered 948 publications, after applying the selection criteria, 202 publications were included. The annual number of publications was variable, Brazil was the country with the highest production. 1056 different author signatures were identified, the co-authorship index was 5,2 and the international collaboration rate was 38.6%. 235 institutional affiliations from 23 different countries are identified. The University of São Paulo was the most productive institution. The journal AIDS and Behavior accounted for 7% of the publications. Conclusion. In a period of 13 years, the production of original publications about ART in Latin America and the Caribbean was 202. Brazil is a relevant production center in research on this specific topic of the study of HIV.